1990
DOI: 10.1007/bf02335556
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia due to lesions confined to the right hemisphere in right handed patients: a review of the literature including the Italian cases

Abstract: We review most of the work published, to our knowledge, between 1880 and 1988 on aphasia due to right cerebral lesions in right-handed patients ("crossed aphasia"). We summarize the 87 cases found in chronological order within defined groups, dealing in greater detail with the less well-known cases in English-language publications and with the cases from other sources that we consider most representative and convincing. The 87 cases fall into three groups on the following criteria: right-handedness (on standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…From 1975 on, a starting-point chosen because Faglia, Rottoli, and Vignolo (1990) showed that all fully acceptable CAD cases were published thereafter, we encountered only four dextral children (2.3%) in a corpus of 169 aphasic cases with righthemisphere injury.…”
Section: Introductionmentioning
confidence: 98%
“…From 1975 on, a starting-point chosen because Faglia, Rottoli, and Vignolo (1990) showed that all fully acceptable CAD cases were published thereafter, we encountered only four dextral children (2.3%) in a corpus of 169 aphasic cases with righthemisphere injury.…”
Section: Introductionmentioning
confidence: 98%
“…From 1975, a starting point chosen because Faglia et al (1990) showed that all fully acceptable CAD cases were published thereafter, we gathered from the literature all right-handed patients with an aphasic syndrome following damage to the right hemisphere. From this corpus of 170 cases, enriched with 10 personal observations, all childhood cases were selected.…”
Section: Selection Of Casesmentioning
confidence: 99%
“…Cultural and idiosyncratic factors such as bi-or polyglottism, illiteracy, tonal language use, and use of an ideographic script were introduced in the 1980s as additional exclusion criteria (e.g., Joanette, Puel, Nespoulous, Rascol, & Lecours, 1982). The latest tendency has been to reduce the number of exclusion criteria again to essentially the same criteria as proposed by Brown and Wilson (1973) (e.g., Faglia, Rottoli, & Vignolo, 1990). Brown and Hécaen (1973) were the first to define CAD as a semiologically uniform syndrome.…”
mentioning
confidence: 98%
“…Bei nichtvaskulären Krankheitsbildern (z. B. Hirntumoren [9,10], Epilepsien [11], Schädel-Hirn-Traumata [12], neurodegenerativen Erkrankungen [13], Fallübersichten bei [14,15]), ist es aufgrund unterschiedlicher zugrunde liegender Pathomechanismen besonders wichtig, mittels suffizienter (ggf. auch funktioneller) Bildgebung definitiv (subklinische) linkshemisphärische Läsionen auszuschließen, bevor eine gekreuzte Aphasie diagnostiziert wird [16].…”
Section: Introductionunclassified